Water Bill Perception in Brazil: Do Households Get It Right? - María Pérez; Jesse Libra; Kleber Machado; Tomás Serebrisky; Ben Solís (Inter-American Development Bank (IDB), 2022)
An issue that affects the effectiveness of water pricing policies is consumers misperception, which implies that households decide their water consumption based on poor/inaccurate information about the marginal price. We use household survey data on bill and quality perception in Brazil to analyze this problem and its drivers. Once we control for the selection bias caused by survey respondents voluntarily providing their bill, we find evidence of bill misperception. Apart from the informational and socioeconomic drivers usually considered in the literature, perceived water quality seems to be a relevant factor of the degree of misperception.
Keywords: Q21; Q25; Q54; 330; water pricing; water quality; price perceptions; economics of information